Meningkatkan Kreativitas Dan Nilai Hasil Belajar PAI Materi Menghindarkan Diri Dari Pergaulan Bebas Dan Perbuatan Zina Melalui STAD: Di SMK Negeri 3 Linggabuana - Suherman, Tatang (Universitas Cokroaminoto Yogyakarta, 2023)
The purpose of the study was to improve the learning process, creativity and learning outcomes of class X PSPT students at SMK Negeri 3 Linggabuana using the STAD cooperative learning model. The type of research is classroom action research. Research subjects 34 students. Data collection techniques with observation, test and documentation techniques. Data validation is democratic, process, and dialogic validation. Quantitative data analysis techniques. Increased learning creativity of 10 students (29.41%) in the initial conditions, to 20 students (58.82%) in the first cycle and 31 students (91.18%) in the last cycle from the limit of 85% increased learning creativity. The data for learning completeness in the initial conditions were 7 students or 20.59%. In the first cycle 17 students (50.00%) and in the second cycle 30 students (88.24%) from the limit of 85% the number of students was declared complete. The increase in the average value of learning outcomes was 55.88 in the initial conditions, increased by 68.24 in the first cycle and 81.47 in the second cycle from the KKM = 75 limit.